Institutional challenges and opportunities for encouraging transit-oriented development with bus rapid transit in Lahore, Pakistan - Muhammad Nadeem; Mihoko Matsuyuki (Transportation Research Interdisciplinary Perspectives)
Transit-oriented development (TOD) includes dense, mixed-use, and pedestrian-friendly developments around transit stations. Bus rapid transit (BRT) stimulates TOD in developed countries through comprehensive planning and governance, while limited infrastructure, weak institutions, and fragmented policies hinder the ability of the BRT system to encourage TOD in developing countries. Therefore, our study aimed to understand the institutional challenges and opportunities that stand in the way of TOD coupled with BRT in Lahore, Pakistan. To this end, we used a qualitative analysis of semistructured interviews in NVivo 14 with nine professionals from land-use and transportation institutions. Our study considered five influential factors to understand the institutional challenges and opportunities in promoting BRT-based TOD: the regulatory framework, institutional responsibilities, institutional coordination, local expertise, and incentives. Results show that the foremost challenges are the absence of a regulatory framework, functional overlap, lack of institutional coordination, low government priority and political will, limited expertise and leadership, and absence of incentives. We conclude that multiple institutions contribute to land-use and transportation planning; however, their relationship and influence on TOD are weak. Our study suggests that a clear regulatory framework, TOD plans, TOD-specific zoning, enhanced institutional coordination, local expertise, strong political will, professional capacity, visionary leadership, effective public–private partnership, and targeted incentives are essential to promote TOD through BRT.